PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING KARYAWAN PERUMNAS SEMARANG - Anggara Hapsari; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2019)
PERUMNAS is a State-Owned Enterprise (SOE) in the form of Public Corporation (Perum) whereby all of its shares are owned by the Government. This research was conducted at the Office of Perum Perumnas Regional V Branch Semarang on Jalan Wilis No. 23Semarang. This study aims to determine the effect of Job Satisfaction Variables and Organizational Commitment to Employee Performance through Organizational Citizenship Behavior (OCB) as Intervening Variable. The type of research is explanatory research. The population is all employees of Perumnas Regional V Branch Semarang with the number of 43 people and using saturated sample technique. Data were analyzed by qualitative and quantitative analysis by using coefficient of determination test, simple and multiple linear regression, classical assumption test, goodness of fit test, path analysis, and test sobel. The results showed that job satisfaction has no significant effect on OCB or employee performance. Unlike organizational commitment variables that have the greatest role in influencing OCB and employee performance.